Menuju Demokrasi Rasional: Melacak Pemikiran JÃ¼rgen Habermas tentang Ruang Publik - Prasetyo, Antonius Galih (Jurnal Ilmu Sosial dan Ilmu Politik, 2012)
As a concept widely employed to promote the deeper and more radical democracy within the framework of deliberative democracy, public sphere as formulated by JÃ¼rgen Habermas in his two books, The Structural Transformation of Public Sphere and Between Facts and Norms, acts as a crucial theory to investigate and assess the degree of publicness in todayâs democracy discourse. This paper aims to elaborate the concept of public sphere as written in those two books. By comparing the content of each book, this paper also classifies the similarity and differences between the concept of public sphere written in those two texts.